Translation and adaptation of rating scales - Sandeep Grover; Vikas Menon; Snehil Gupta; K Vidhukumar; P V Indu; Deenu Chacko (Indian Journal of Psychiatry)
Rating scales are key to any quantitative research in psychiatry. It is essential to recognize that rating scales developed in one language and cultural context may not directly apply to another. A literal translation may not be sufficient for valid results, as this does not reflect the conceptual equivalence. Therefore, it is essential to translate and adapt rating scales developed in one language to another to ensure the development of a translated scale with good conceptual equivalence to the original scale. This article covers the various types of translations, the translation procedures, and the steps involved in translating and adapting rating scales.